STEM, Robotics, Mobile Apps in Early Childhood and Primary Education Technology to Promote Teaching and Learning - Papadakis, Stamatios; Kalogiannakis, Michail (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book brings together a collection of work from around the world in order to consider effective STEM, robotics, mobile apps education from a range of perspectives. It presents valuable perspectives-both practical and theoretical-that enrich the current STEM, robotics, mobile apps education agenda. As such, the book makes a substantial contribution to the literature and outlines the key challenges in research, policy, and practice for STEM education, from early childhood through to the first school age education. The audience for the book includes college students, teachers of young children, college and university faculty, and professionals from fields other than education who are unified by their commitment to the care and education of young children.
Part 1: Preschool Education Domain -- Part 2: Technological Tools, STEM, Robotics and Mobile Apps -- Part 3: Pedagogy, Strategy and Creative Approach -- Part 4: In Service and Per-Service Teachers' perceptions -- Part 5: Students and Parents Perceptions -- Part 6: Issues, Challenges and Trends.
Keywords: Educational technology; Teaching; Early childhood education; Science-Study and teaching; Digital Education and Educational Technology; Pedagogy; Early Childhood Education; Science Education